PENGARUH PROMOSI JABATAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA BANK X TEUKU UMAR KOTA BANDUNG - fachri, ilyasa kautsar (Journal of Business Management Education (JBME), 2020)
This study aims to find a description of job promotions, know the description of employee job satisfaction, know the description of employee performance, determine the effect of job promotion and job satisfaction on employee performance. The object of the unit of analysis in this study is the employee of Bank X Teuku Umar, Bandung. Variable (X1) in this study is promotion, variable (X2) job satisfaction, and variable (Y) is employee performance. The type of research used is descriptive and verification. The method used was an explanatory survey with a sample of 77 respondents. Data analysis technique used is multiple regression with statistical software for service solutions (SPSS) 24.0 for Windows. The findings in this study indicate that the description of promotion in the high category, a description of job satisfaction in the strong category, a description of employee performance in the high category. Based on the results of this study, in the promotion of the position it is recommended that improvements be made to the dimensions of job satisfaction in co-workers that need to be improved and deepened, so that employee performance can improve. In job satisfaction Bank X Teuku Umar Bandung City employees need to be improved in employee performance, where employees must be able to communicate better with colleagues. So it is expected that the employees of Bank X Teuku Umar in Bandung can increase their promotions and increase job satisfaction so that employee performance becomes more effective and efficient.